If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.4x + -12 = -22 Reorder the terms: -12 + 0.4x = -22 Solving -12 + 0.4x = -22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 0.4x = -22 + 12 Combine like terms: -12 + 12 = 0 0 + 0.4x = -22 + 12 0.4x = -22 + 12 Combine like terms: -22 + 12 = -10 0.4x = -10 Divide each side by '0.4'. x = -25 Simplifying x = -25
| 758+8=750 | | .25x+-0.5=15-x | | 750+8=742 | | -2x-(-4y)=1 | | 3c-5+2c= | | 6t=15 | | -10+7=x+4+4 | | -5=v/16 | | 12x^4-480x^2-4500=0 | | 5x-35=20 | | 10y+3=8y+10 | | 3x+-2.4=-2 | | x-(7-3x)+5=2x+10 | | 3x+17+5=7x+10 | | 2/3q-2=1/3q+7 | | -45+n=44 | | B+4=-1b | | x^3+x^2+2x-20=0 | | 6(1X+3)=24 | | 0.5(P+8)=q | | f(x)=15-1 | | 2m+2n-5= | | 4x+32=20x | | 3x+1=-3x+31 | | ln(x^2)=9 | | -5/8+83/8= | | 4p+8-3p= | | 750+8=758 | | 28=(3x+4)*4 | | 4x+-2=2(x+-6) | | 3(2x+5)=ax+5 | | 4(5x+2)-6x=5(2x+4) |